Promoting social and blue entrepreneurship and sustainability skills in higher education by transversal competencies. - Lechuga-Jiménez, Clotilde; Barroso, María-Belén; García-Cheikh-Lahlou, Enrique Alastor; Tójar-Hurtado, Juan Carlos (Taylor & Francis, 2024)
This study examines the presence of “Effective Communication” (EC) and “Teamwork/Cooperative Learning” (TW&CL) competencies in undergraduate university programmes using a blue entrepreneurship approach, within the framework of a social and sustainable economy. As seen in previous studies, these two competencies are highly relevant to promote sustainable and blue entrepreneurship in undergraduate programmes. Eighty-one curricula were collected in nine Spanish public universities in southern Spain. QUAN (qual)→QUAL mixed methodology was used, which included a qualitative analysis and a quantitative comparative analysis form, aiming to build theoretical frameworks through explanatory diagrams to understand how EC and TW&CL are promoted in university programmes. The study found that EC and TW&CL competencies are highly valued and widely incorporated in university curricula. The qualitative analysis revealed the components and interconnections of these competencies, highlighting the importance of effective communication, critical thinking, and interdisciplinary teamwork. The survey shows the complementary nature of EC and TW&CL and suggests their integration in educational contexts. This study therefore contributes to the recognition of these specific competences in university degrees by providing data on their presence, type and relationships, so that educational institutions can better prepare students for future careers.
Keywords: Investigación activa en educación; Enseñanza superior; Competencia en educación; Higher education; Competencies; Effective communication; Teamwork; Cooperative learning